The positive value of personality. Pavel Novgorodtsev’s legal idealism - Daniłkina, Natalia (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
Pavel Novgorodtsev was a professor of jurisprudence, politician, and a major representative of Russian philosophy of law. At the turn of the 20th century he recognised a crisis of the positivist juridical doctrine and an increased demand in the philosophy of law, which he identified as the doctrine of natural law. According to Novgorodtsev, the new doctrine of natural law was to embrace a set of moral concerns about the existing law. He elaborated his conception on a basis of broadly construed philosophical idealism – from Kant to philosophically “modernised” Russian Christian orthodoxy. The paper outlines Novgorodtsev’s philosophy of law and reveals its specific features in comparison with relevant west-European theories, as well as in connection with a pronounced personalistic trend in Russian philosophy.